A Topic-Based Diachronic Account of the Polysemy of the English Verb ‘Run’ - Kiyama, Naoki; Shibuya, Yoshikata (Research in Language, 2023)
This study discusses the polysemy and diachronic semantic frequency shifts of the English verb run using a topic model. The increase in corpus-based research in cognitive linguistics has yielded many empirical findings on various aspects of language. However, there are still areas that have not received sufficient attention. One such area is the study of word meaning in terms of related topics and social interest. In this paper, we analyze diachronic data collected from the NOW corpus (News on Web) and argue that the polysemy of run can be described in terms of topic, and that the change in the use of the meanings that this verb has can be described in terms of a change in social interest.